Development of a Cost-Effective Plasma Thawer: A Potential Game-Changer in Blood Transfusion Technology - Shamrez Shahid; Muhammad Danish Mujib Mujib; Ahmad Zahid Rao; Muhammad Abul Hasan; Saad Ahmed Qazi (Sukkur IBA Journal of Emerging Technologies)
Plasma thawers are vital in healthcare, ensuring safe thawing of frozen plasma for life-saving transfusions. To address challenges such as specialized operator training and high initial costs in low-resource settings, we developed a cost-effective and efficient plasma thawer in Pakistan. The device consisted of two compartments: one dedicated to thawing plasma and equipped with a water-filled heater, a continuous temperature sensor, and an agitating frame for plasma bags, and the other housing the control box. Optimized thawing conditions were defined. The regulation of temperature and control of motors were coordinated through an Arduino microcontroller and relays which allowed users to set temperature limits through push buttons. Our device was able to thaw frozen plasma, accurately maintaining water temperature between 37-40°C. The samples were clear of solid and gelatinous particles, indicating no protein denaturation or overheating. A buzzer signaled the completion of each cycle. The microcontroller cut off power to the heater if the temperature exceeded the upper limit. Relays activated heater to maintain water temperature above the lower limit and activated DC motor which converted rotational motion into linear motion through gears. The device was 10 times more cost-effective compared to commercially available alternatives. We demonstrated that plasma can be thawed using our prototype without any negative influence on the plasma quality, presupposed that optimized settings defined for this plasma product are used. We plan to further assess plasma coagulation, inhibition activity and hemostatic potency.